2005
DOI: 10.1016/j.jvs.2004.11.033
|View full text |Cite
|
Sign up to set email alerts
|

In vivo and mechanical properties of peritoneum/fascia as a novel arterial substitute

Abstract: The search for an artificial, thromboresistant, and intimal hyperplasia resistant interface between blood and native blood vessels still continues. This study demonstrates the feasibility and proof of concept of the peritoneum's clot-resistant properties. When adding the underlying fascia, it serves as an ideal arterial patch. Other studies are underway evaluating its feasibility as a bypass graft and a "drug coated"-like stent lining.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 13 publications
3
17
0
Order By: Relevance
“…Pena and Husni, in 1968, compared autogenous vein with Dacron in femoral artery patch angioplasty on dogs, and the time course of the study ranged from 2 weeks to 9 months. 20,25,31 In the present study, there were no clinical complications. The results were confirmed through clinical evaluation, Doppler fluxometry, angiography, and the measure of femoral vein diameter.…”
Section: Discussionsupporting
confidence: 43%
See 1 more Smart Citation
“…Pena and Husni, in 1968, compared autogenous vein with Dacron in femoral artery patch angioplasty on dogs, and the time course of the study ranged from 2 weeks to 9 months. 20,25,31 In the present study, there were no clinical complications. The results were confirmed through clinical evaluation, Doppler fluxometry, angiography, and the measure of femoral vein diameter.…”
Section: Discussionsupporting
confidence: 43%
“…The major complications with the use of the patches are similar to those of the other kind of arterial substitutes: thrombosis, rupture or pseudoaneurysm formation, and operatory wound infection. [20][21][22][23][24][25][26][27] The rate of aneurismal formation and resistance to rupture of bovine pericardium, Dacron, PTFE, and greater saphenous vein have been reported in the literature. Biasi et al, in 2002, reported no cases of rupture or aneurismal formation by the use of bovine pericardium patch angioplasty during carotid endarterectomy in 323 cases.…”
Section: Discussionmentioning
confidence: 99%
“…One other biomaterial that has been reported after use in an animal study is a combination patch, with one side of the patch constructed from glutaraldehyde-fixed bovine peritoneum/fascia, and the other side constructed from polyester 54. This interesting patch was tested in femoral arteries of dogs and found to have, at 6 months, no degeneration and complete reendothelialization; the mechanical strength was superior to that of bovine pericardial patches.…”
Section: Types Of Patchesmentioning
confidence: 99%
“…For these reasons, the parietal peritoneum has been proposed as a vascular substitute. For instance, Sarac et al studied a fascia-peritoneum patch as a pledget for an infected aortic stump [11] and as an arterial substitute in femoral artery patch angioplasty on dogs [12]. Garcia-Graz et al [13] created a vascular autograft with the posterior rectus aponeurosis including the subjacent peritoneum in seven dogs, and performed an implantation on the aorta by an end-to-end surgical anastomosis; to avoid the dilatation of the graft the authors encircled the fasciaperitoneum with three rings made of a 3/0 silk floss.…”
Section: Introductionmentioning
confidence: 99%